Spending for success: identifying 'what works?' for Indigenous student outcomes in Australian Universities. Issue 2 (28th December 2021) - Hearn, Shane; Kenna, Liam
Abstract: Despite the continued investment in Indigenous support networks and dedicated education units within universities, levels of key performance indicators for Indigenous students—access, participation, success and completion (attainment)—remain below that of the overall domestic student population in most institutions. It remains important to determine what works to achieve Indigenous student success in higher education. This paper proposes that such methods have an integral role to play in providing a holistic view of Indigenous participation and success at university, and are particularly useful in the development and evaluation of strategies and programs. This project found no quantitative correlation between financial investment and success rate for Indigenous students. A negative correlation between access rate and success rate suggests that factors other than those that encourage participation are important in supporting successful outcomes. Those universities that have high success rates have a suite of programs to support Indigenous students, but it is not immediately clear which of these strategies and programs may be most effective to facilitate Indigenous student success rates. In this discussion, we suggest that a multi-layered determinants model is a useful way to conceptualise the many factors that may impact on student success, and how they might intersect.